THE POTENTIAL OF ARTIFICIAL INTELLIGENCE IN SOUTH AFRICAN MANUFACTURING - Greef, A.R.; Reinecke, R. (The South African Journal of Industrial Engineering, 2011)
This paper provides an introduction to the most commonly used Knowledge Based Systems (KBS’s) called Rule Based Systems, presents some benefits of using these systems if the application warrants their attention and provides an over-view of current R&D as well as industrial systems already implemented. Areas of manUfacturing that could use KES’s within the South African context are suggested. A research programme investigating the use of KBS’s in robotics in progress at the University of Stellenbosch demonstrating a number of useful properties associated with programming Artificial Intelligence (AI) techniques using logic programming, is discussed.